Precise Carrier Diagnosis in Families with Haemophilia A: Use of Conformation Sensitive Gel Electrophoresis for Mutation Screening and Polymorphism Analysis - Williams, I. J.; Abuzenadah, A.; Winship, P. R.; Preston, F. E.; Dolan, G.; Wright, J.; Peake, I. R.; Goodeve, A. C. (Thrombosis and Haemostasis, 1998)
Causative mutations in the factor VIII gene of seven unrelated patients with severe haemophilia A were identified using the mutation screening procedure conformation sensitive gel electrophoresis (1) and characterised by direct sequencing. Female family members of all patients had requested either carrier status determination or prenatal diagnosis. However, lack of the factor VIII gene inversion, a prior family history or informative polymorphisms prevented diagnosis in these families. Identification of a mutation in each family enabled female carrier status to be determined in all cases. Six mutations were previously unreported. One Afro-Caribbean patient had two sequence changes; A670 2G and A6769G. The latter, resulting in Met2238Val and previously reported as a FVIII mutation, was shown to be polymorphic with a 42% heterozygosity rate in an Afro-Caribbean population. Conformation sensitive gel electrophoresis was found to be technically simple and efficient at locating previously unknown FVIII gene mutations.